2020
DOI: 10.1037/cap0000182
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of the Static-99R and Static-2002R risk tools for identifying Indigenous and White individuals at high risk for sexual recidivism in Canada.

Abstract: In Canada, the issue of cultural bias in risk assessment tools is an ongoing concern, particularly for Indigenous peoples who are overrepresented in the criminal justice system. To date, there has been relatively little research on structured risk assessment tools for Indigenous peoples. This study examined the predictive accuracy of two sexual recidivism risk tools (Static-99R, Static-2002R) for White individuals (n = 1,560) and persons of Indigenous heritage (n = 653) from five independent Canadian samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
(95 reference statements)
1
37
1
Order By: Relevance
“…Conversely, there are also reasons to expect similar risk factors across countries, when the same type of criminal behavior is considered. In this sense, risk assessment tools, such as Static-99R (Hanson & Thornton, 2000), have shown consistent discrimination across intercultural samples (e.g., Static-99R predicted sexual recidivism among US-born Latinos; Leguízamo et al, 2017; American individuals with Black heritage; Lee & Hanson, 2017; and Indigenous peoples in Canada; Lee et al, 2019), which suggest CPORT could also evidence cross-cultural validity.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there are also reasons to expect similar risk factors across countries, when the same type of criminal behavior is considered. In this sense, risk assessment tools, such as Static-99R (Hanson & Thornton, 2000), have shown consistent discrimination across intercultural samples (e.g., Static-99R predicted sexual recidivism among US-born Latinos; Leguízamo et al, 2017; American individuals with Black heritage; Lee & Hanson, 2017; and Indigenous peoples in Canada; Lee et al, 2019), which suggest CPORT could also evidence cross-cultural validity.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the discharged and still committed samples, average Static-99R scores for other racial/ethnic categories (M = 3.76; SD = 1.37) was higher compared to Non-Hispanic White participants (M = 3.28; SD = 1.99), although this difference was not statistically significant and the effect size was small in magnitude (p = 0.31, d = 0.28). Black participants have scored higher than White participants on the Static-99R in several other studies (Hanson et al, 2014;Lee & Hanson, 2017;Lee, Hanson, & Blais, 2020;Varela et al, 2013). Racial differences in risk factors and static risk scores could be explained by a variety of factors, including social inequities, disadvantaged environments, cultural factors, and systemic bias within the criminal justice system (Hart, 2016;Lee, Hanson, & Blais, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…Modern evaluators have a variety of instruments to choose from (see Kelley et al, 2020; Neal & Grisso, 2014) and Allan et al (2018) identified 11 instruments Australian evaluators use, including actuarial (e.g., the STATIC-99; Hanson & Thornton, 1999) and structured professional judgment assessment (e.g., The Risk for Sexual Violence Protocol [(RSVP]; Hart et al, 2003) instruments. Researchers nevertheless consistently find that ancestry (i.e., line of descent) and/or culture influence the predictive accuracy of these instruments (e.g., Allan et al, 2006; Babchishin et al, 2012; Gutierrez et al, 2013, 2016; Långström, 2004; Lee et al, 2020; McCuish et al, 2018; Perley-Robertson et al, 2018; Smallbone & Rallings, 2013; Spiranovic, 2012; Wormith et al, 2015). These findings have significant practical, ethical and legal implications for evaluators who work in countries with notable Indigenous populations (e.g., Allan, 2018, 2020; Allan et al, 2006; Hart, 2016; Olver, 2016; Shepherd, 2016; Shepherd et al, 2014, 2017; Shepherd & Lewis-Fernandez, 2016).…”
mentioning
confidence: 99%